Pengaruh Online Review dan Product Rating terhadap Keputusan Pembelian pada Produk Elektronik di Tokopedia - Vivi Vivi; Steven Steven; Desma Erica Maryati Manik (Jurnal Manajemen Bisnis Era Digital, 2026)
This study is motivated by the dynamic changes in digital consumer behavior in e-commerce, particularly in the purchase of electronic products through the Tokopedia platform. The study aims to analyze and synthesize the influence of online reviews and product ratings on purchase decisions using a systematic literature review approach. The method involves a comprehensive examination of global and local scientific literature, with a focus on peer-reviewed journals and empirical studies published between 2021 and 2026. The findings indicate that online reviews and product ratings are capable of reducing consumer uncertainty as well as the functional risks associated with electronic products. Empirical evidence over the past decade suggests that high ratings can build initial confidence in brand quality, while detailed reviews provide crucial technical validation for potential buyers. Overall, these two indicators work synergistically to strengthen consumer trust and serve as key determinants in the final stage of the purchasing decision. The implications suggest that e-commerce platforms and sellers need to prioritize the management of user-generated content and maintain transparency in reputation to remain competitive in a market increasingly reliant on the credibility of online information.